PPEELLAAKKSSAANNAAAANN PPEENNDDIIDDIIKKAANN DDAANN PPEELLAATTIIHHAANN KKEEPPEEMMIIMMPPIINNAANN ((DDIIKKLLAATTPPIIMM)) IIVV DDII BBAADDAANN KKEEPPEEGGAAWWAAIIAANN DDAAEERRAAHH ((BBKKDD)) PPEEMMEERRIINNTTAAHH KKAABBUUPPAATTEENN RROOKKAANN HHUULLUU - Nadya Vinandari; Muhammad Ridwan (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2015)
IImmpplleemmeennttaattiioonn LLeeaaddeerrsshhiipp EEdduuccaattiioonn AAnndd TTrraaiinniinngg ((DDiikkllaattppiimm)) IIVV IINN RReeggiioonnaall PPeerrssoonnnneell AAggeennccyy ((BBKKDD)) GGoovveerrnnmmeenntt RRookkaann HHuulluu.. TThhee ppuurrppoossee ooff tthhiiss ssttuuddyy iiss ttoo ddeetteerrmmiinnee wwhhyy tthhee iimmpplleemmeennttaattiioonn ooff EEdduuccaattiioonn aanndd LLeeaaddeerrsshhiipp TTrraaiinniinngg IIVV ffoorr llooccaall ggoovveerrnnmmeenntt ooffffiicciiaallss iinn RRookkaann HHuulluu ccaann nnoott bbee iimmpplleemmeenntteedd pprrooppeerrllyy.. TThhiiss ssttuuddyy uusseess ddaattaa ccoolllleeccttiioonn tthhrroouugghh iinntteerrvviieewwss,, ddooccuummeennttaattiioonn aanndd oobbsseerrvvaattiioonn.. DDaattaa wweerree aannaallyyzzeedd uussiinngg ddeessccrriippttiivvee qquuaalliittaattiivvee mmeetthhoodd.. PPrriimmaarryy ddaattaa,, iiee ddaattaa oobbttaaiinneedd ffrroomm iinntteerrvviieewwss wwiitthh iinnffoorrmmaannttss rreesseeaarrcchh oonn tthhee iimmpplleemmeennttaattiioonn ooff tthhee EEdduuccaattiioonn aanndd TTrraaiinniinngg PPiimm IIVV,, wwhhiillee tthhee sseeccoonnddaarryy ddaattaa,, iiee tthhee ddaattaa iinn tthhee ffoorrmm ssoo tthhaatt hhaass bbeeeenn oowwnneedd bbyy tthhee OOffffiiccee ooff tthhee RReeggiioonnaall EEmmppllooyymmeenntt BBooaarrdd RRookkaann HHuulluu iinncclluuddee:: aa bbrriieeff hhiissttoorryy,, oorrggaanniizzaattiioonnaall ssttrruuccttuurree aanndd aaccttiivviittiieess ooff tthhee OOffffiiccee ooff BBKKDD RRookkaann HHuulluu.. TThhiiss ssttuuddyy uusseess rreesseeaarrcchh iinnffoorrmmaannttss aass mmaannyy aass 1122 ppeeooppllee,, wwhheerree rreesseeaarrcchheerrss hhaavvee uunnddeerrssttoooodd tthhee iinniittiiaall iinnffoorrmmaattiioonn aabboouutt tthhee oobbjjeecctt ooff rreesseeaarrcchh aanndd rreesseeaarrcchh iinnffoorrmmaannttss.. TThhee rreessuullttss bbaasseedd oonn iinntteerrvviieewwss aanndd ffiieelldd oobbsseerrvvaattiioonnss iinn mmiinndd tthhaatt wwhhyy tthhee iimmpplleemmeennttaattiioonn ooff tthhee EEdduuccaattiioonn aanndd TTrraaiinniinngg LLeeaaddeerrsshhiipp IIVV ffoorr llooccaall ggoovveerrnnmmeenntt ooffffiicciiaallss iinn RRookkaann HHuulluu ccaann nnoott bbee iimmpplleemmeenntteedd pprrooppeerrllyy bbeeccaauussee nnoott aallll ooff tthhee ssttaaggeess iinn tthhee ccuurrrriiccuulluumm ssttrruuccttuurree PPiimm IIVV TTrraaiinniinngg ccaann bbee ddoonnee wweellll iinn wwhhiicchh ffoouurr ssttaaggeess nnaammeellyy SSttaaggeess LLaabboorraattoorryy lleeaaddeerrsshhiipp ccaann nnoott bbee ddoonnee llaatteerr LLeessss ssppeecciiffiiccaallllyy BBKKDD RRookkaann HHuulluu iinn rreeccrruuiittiinngg ppaarrttiicciippaannttss PPiimm IIVV TTrraaiinniinngg ffrroomm eecchheelloonn IIVV ooffffiicciiaallss bbuutt hhaass yyeett ttoo ffoollllooww PPiimm IIVV TTrraaiinniinngg aanndd mmaaxxiimmuumm nnoo pprraaccttiiccee sseessssiioonn wwaass hheelldd oonn TTrraaiinniinngg PPiimm IIVV,, tthhiiss iiss dduuee ttoo tthhee lliimmiitteedd ffaacciilliittiieess aanndd iinnffrraassttrruuccttuurree oowwnneedd bbyy BBKKDD RRookkaann HHuulluu ttoo ccoonndduucctt pprraaccttiiccee sseessssiioonnss ffoorr tthhee aapppplliiccaattiioonn ooff tthhee tthheeoorriieess bbeeiinngg ssttuuddiieedd bbyy tthhee ppaarrttiicciippaannttss dduurriinngg tthhee ttrraaiinniinngg..KKeeyywwoorrddss:: EEdduuccaattiioonn aanndd TTrraaiinniinngg,, EEdduuccaattiioonn aanndd LLeeaaddeerrsshhiipp TTrraaiinniinngg IIV